EFEITO DA CALAGEM E FERTILIZAÇÃO SOBRE O DESENVOLVIMENTO DE MUDAS DE ERVA-MATE (ILEX PARAGUARIENSIS A. ST.HIL.) - Coelho, Geraldo C.; Escaio, Ana C.; Schock, Anderson A.; Libardoni, Juliana B.; Fernandes, Sandra B. V.; Quadros, Valmir (Salão do Conhecimento, 2013)
Resumo